The Influence of Unionism Upon Earnings - Ross, Arthur M. (Quarterly Journal of Economics, 1948)
Introduction: scope of the paper, 263. — I. Unionism and earnings, 1933–45: the data, 264; analysis of relative wage movements, 267. — II. Alternative hypotheses: differences in skill, 274; urban and rural industries, 275; proportion of women, 276; degree of monopoly, 277; expanding and contracting industries, 277; summary of these considerations, 279. — III. Unionism and earnings, 1890–1926: Douglas' data, 280; appraisal of the indexes, 281; a more fundamental objection, 282. — IV. Implications, 284.